The impact of cigarette smoking and smoking cessation on risk and phenotype of rheumatoid arthritis - E. G. Zotkin; E. V. Pozhidaev; A. V. Gordeev (Научно-практическая ревматология, 2024)
Literature review presents the data of recent scientific studies aimed to analyze the impact of cigarette smoking on the risk of rheumatoid arthritis (RA). It is shown the main mechanisms of interaction between genetic constitution, synthesis of RA-specific antibodies, and other immune trait under the influence of cigarette smoke in patients with RA. We presented summarized data indicating the positive effect of smoking cessation in RA patients.